2022
DOI: 10.3389/fendo.2022.929572
|View full text |Cite
|
Sign up to set email alerts
|

The systemic-level repercussions of cancer-associated inflammation mediators produced in the tumor microenvironment

Abstract: The tumor microenvironment is a dynamic, complex, and redundant network of interactions between tumor, immune, and stromal cells. In this intricate environment, cells communicate through membrane–membrane, ligand–receptor, exosome, soluble factors, and transporter interactions that govern cell fate. These interactions activate the diverse and superfluous signaling pathways involved in tumor promotion and progression and induce subtle changes in the functional activity of infiltrating immune cells.The immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 331 publications
0
19
0
Order By: Relevance
“…This scenario could be explained as primary-derived colorectal tumourspheres efficiently responding to oxaliplatin treatment, maintaining tumoursphere formation but also increasing CSCs and stemness marker mRNA expression. It is worth noting that tumoural cells change the tissue architecture, which causes stress in the cells of stroma and induces the release of soluble inflammatory mediators and growth factors [ 12 , 15 ]. These factors maintain an inflammatory microenvironment, promoting tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This scenario could be explained as primary-derived colorectal tumourspheres efficiently responding to oxaliplatin treatment, maintaining tumoursphere formation but also increasing CSCs and stemness marker mRNA expression. It is worth noting that tumoural cells change the tissue architecture, which causes stress in the cells of stroma and induces the release of soluble inflammatory mediators and growth factors [ 12 , 15 ]. These factors maintain an inflammatory microenvironment, promoting tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mechanisms are mediated by different immune cells through different cytokines, chemokines, and other proinflammatory molecules, which trigger cell progression, hyperplasia, and metastasis [ 14 , 15 ]. These inflammatory mechanisms are mediated by interleukins and their receptors, creating an interconnection between tumour and immune cells [ 15 ].…”
Section: Introductionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes, saucer-shaped extracellular vesicles of approximately 30–100 nm diameter that are delimited by a lipid bilayer, contain a large amount of biologically active molecules, such as lipids, enzymes, metabolites, and various non-coding RNAs (miRNAs, long noncoding RNAs, and circular RNAs) ( Yu et al, 2021 ), and play important roles in cell-cell communications in TME ( Aguilar-Cazares et al, 2022 ; Ghosh and Ghosh, 2022 ). In addition, due to the excellent biosafety, low immunogenicity, carrier properties, nanoscale penetration effect, longer half-life, and no microvascular embolism ( Ghosh et al, 2020 ), numerous studies have shown that as a carrier of conventional chemotherapy drugs ( Zhao et al, 2021 ; Premnath et al, 2022 ), targeted therapy ( Deng et al, 2021 ; Xu et al, 2021 ), or mediate photodynamic therapy and immunotherapy ( Jang et al, 2021 ), exosomes have shown potential as a new NDDS for the treatment of PC.…”
Section: Discussionmentioning
confidence: 99%